Pemahaman Syariah dan Aplikasinya dengan Kenyataan Real di Indonesia - Alfiandi Zikra; Dhiauddin Tanjung (Departement of Mathematics Education, 2023)
This study aims to explain the understanding of sharia and the impact of misunderstandings in understanding sharia in Indonesia. This study includes a qualitative study model with data collection techniques based on reference sources in the library and scientific references relevant to this title. Sharia is a basic legal norm that has been established by Allah which must be followed by Muslims based on faith related to morality, both related to their relationship with Allah and with fellow human beings. Sharia is actually the comprehensive teachings of the Islamic religion itself which contains provisions and rules of law and ethics which are all beneficial for the happiness of life in the world and the hereafter, but in practice the views of many people towards the term sharia are quite diverse and even some of them are quite implied if Leaving history to record at least three views that are misguided in understanding sharia so that it will keep Muslims away from where the true beauty of sharia freedom is: 1) The mistake of assuming that sharia is a variety of cutting hands and the like, 2) Assuming that sharia is only related to worship only 3) Shari'a sentences are only limited to symbols of the sacred and consider this to be quite noble.